Seasonal Prokaryotic Community Linkages Between Surface and Deep Ocean Water - Wenley, Jess; Currie, Kim; Lockwood, Scott; Thomson, Blair; Baltar, Federico; Morales, Sergio E. (Frontiers in Marine Science, 2021)
Sinking organic particles from surface waters provide key nutrients to the deep ocean, and could serve as vectors transporting microbial diversity to the deep ocean. However, the effect of this seasonally varying connectivity with the surface on deep microbial communities remains unexplored. Here, a three-year time-series from surface and deep (500 m) waters part of the Munida Microbial Observatory Time-Series (MOTS) was used to study the seasonality of epipelagic and mesopelagic prokaryotic communities. The goal was to establish how seasonally dynamic these two communities are, and any potential linkages between them. Both surface and deep prokaryotic communities displayed seasonality with high variation in community diversity. Deep prokaryotic communities mirrored the seasonal patterns in heterotrophic production and bacterial abundance displayed by surface communities, which were related to changes in chlorophyll-a concentration. However, the magnitude of this temporal variability in deeper waters was generally smaller than in the surface. Detection of surface prokaryotes in the deep ocean seemed seasonally linked to phytoplankton blooms, but other copiotrophic or typically algal-associated surface groups were not detected in the mesopelagic suggesting only specific populations were surviving the migration down the water column. We show transfer of organisms across depths is possibly not always unidirectional, with typically deep ocean microbes being seasonally abundant in surface waters. This indicates the main mechanism linking surface and deep communities changes seasonally: sinking of organic particles during productive periods, and vertical convection during winter overturning.